2016
DOI: 10.1051/radiopro/2015034
|View full text |Cite
|
Sign up to set email alerts
|

Connaissances des travailleurs en radioprotection – Enquête au CHU Mongi Slim à La Marsa (Tunisie)

Abstract: -Le but de notre travail était d'évaluer les connaissances en radioprotection du personnel hospitalier directement affecté aux travaux sous rayonnements ionisants (DATR). Nous avons réalisé une étude descriptive transversale, auprès de ce personnel dans les salles opératoires d'orthopédie, de cardiologie interventionnelle et du service de radiologie diagnostique et interventionnelle de l'hôpital Mongi Slim à la Marsa (Tunisie), en utilisant un questionnaire. Le score global des connaissances (SGC) a été calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
(18 reference statements)
0
3
1
2
Order By: Relevance
“…Unlike some studies [6], [9], [18], [19] we observed no influence of professional category or years of practice on any of calculated scores (table 3), especially on RPKS, which is the main object of our study. As residents and interns are numerous in our study population (50%), one might think that they were at the origin of this low level of knowledge, because of their limited professional experience, but they had no statistically significant difference with their elders (p = 0.45) (table 3).…”
Section: Discussioncontrasting
confidence: 85%
“…Unlike some studies [6], [9], [18], [19] we observed no influence of professional category or years of practice on any of calculated scores (table 3), especially on RPKS, which is the main object of our study. As residents and interns are numerous in our study population (50%), one might think that they were at the origin of this low level of knowledge, because of their limited professional experience, but they had no statistically significant difference with their elders (p = 0.45) (table 3).…”
Section: Discussioncontrasting
confidence: 85%
“…Ces faibles proportions observées sont liées a ̀ la faible connaissance du zonage et a ̀ l'absence de radiomètres dans les installations radiologiques. Aussi, peu de salles disposaient d'un témoin lumineux fonctionnel contrairement à l'étude de Marzouk Moussa et al [9], en Tunisie en 2016, où ils étaient présents à l'entrée de toutes les salles. En effet, les pays du Maghreb sont très en avance par rapport à l'Afrique subsaharienne en termes de respect et d'application des normes de radioprotection.…”
Section: Normes Des Locauxunclassified
“…Lacking any validated questionnaires for RP, an ad hoc questionnaire was developed based on several bibliographic sources [15,16,19,[26][27][28] and distributed before and after training. The questionnaire was nominative to compare pre/post training responses and included When the x-ray tube is horizontal, you position yourself:…”
Section: Questionnairementioning
confidence: 99%
“…Indeed, team leaders' recognition of RP rules [5] is a determinant factor. In addition to occupational practices, studies have shown that knowledge in RP is not well known by OR staff [16][17][18] and is even lower amongst radiologists [19]. Many OR professionals request be trained in RP [14,19] and they are aware [20] of radiological hazards, especially radiation-induced cataracts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation